Stockpile Volume Estimation Calculation Based on Terrestrial Laser Scanner (TLS) Data Acquisition and 3D Surface Visualization - Adkha Yulianandha Mabrur; Feny Arafah; Adi Sulistianto (Journal of Applied Geospatial Information, 2023)
Stock taking is a series of activities to calculate the stock of goods that are still stored in the warehouse to be marketed. There are many activities covered in it, ranging from calculating the number of goods, conducting direct inspections, and structuring that will facilitate business operations when a certain product is needed. One of these activities is also carried out in the mining sector. Coal stock-taking is a survey activity carried out in the coal yard area to calculate the volume of the stockpile and coal tonnage after being multiplied by the density value. Large-dimensional coal stocking must be carried out quickly, accurately and in detail. The need for this can be obtained using laser scanner technology. Laser scanner is a tool designed to scan the surface of an object and represent it in 3D in the form of a height density point cloud. Based on this, in carrying out stock-taking calculation activities, measurements are needed which mainly aim to find out the stockpile volume and density in the fourth quarter of the Adipala PLTU Coal Yard. Stockpile measurement method using volumetric method. Measurement using a Laser Scanner tool to obtain the shape of the stockpile area is by seizing the entire surface of the Stockpile by setting the resolution of the density of coordinate points (x, y, z) as needed. Tool displacement when measurements are made on every detail of the Stockpile curve. Based on the calculation results, it is known that the volume value of the coal stockpile on the west side coal yard is 121,420,574 m3 and the east side coal yard is 88,230,355 m3 on. The total volume of coal amounted to 209,650,929 m3 then multiplied by the density of the bulk density survey results and obtained the tonnage of 180,384,417 MT.